Intramolecular chemoselective acylation of a suitably substituted isoindole: synthesis of (+/-)-chilenine and (+/-)-deoxychilenine - Wakchaure, Prasad B.; N. P. Argade (Synthesis-Stuttgart, 2011)
Starting from 3,4-dimethoxyhomophthalic anhydride and 6-bromohomopiperonylamine, concise and efficient syntheses of Chilean berberis products chilenine and deoxychilenine have been demonstrated via partially divergent routes by taking advantage of facile air-oxidation of homophthalimide along with intramolecular chemoselective acylation as the key steps.
Keywords: chemoselective acylation; chilenine; deoxychilenine; homophthalic anhydride; isoindole; Total synthesis